The prevention and improvement effects of vitamin D on type 2 diabetes mellitus: evidence from an umbrella review on Meta-analyses of cohort studies and randomized controlled trials - Cheng, Le; Lv, Chenhui; Xue, Lushan; Zhang, Cheng; Wang, Lili; Wang, Xi; Chen, Shuangzhi; Li, Xuemin; Feng, Wenjuan; Xie, Haoran; Zhao, Haifeng (Frontiers in Nutrition, 2024)
Background To clarify whether Vitamin D prevent the occurrence of type 2 diabetes mellitus (T2DM) and improve glucose control in T2DM patients, we conducted this umbrella review, taking into account the inconsistent results of existing Meta-analyses. We aim to reveal the causal relationship between Vitamin D and T2DM through summarizing Meta-analyses of observational studies, and clarify the improvement on glucose control in T2DM patients through summarizing Meta-analyses of RCT studies between Vitamin D supplementation and T2DM patients, especially in T2DM patients with Vitamin D deficiency. Methods We collected the Meta-analyses of observational studies and RCTs in PubMed, Scopus, Embase, Web of Science, and Cochrane. Results 16 Meta-analyses (6 effect sizes for cohort studies and 10 effect sizes for RCTs) were included in the umbrella Meta-analyses. Random-effects model was carried out to calculate the pooled point estimates and their respective 95% confidence intervals (CI). The results revealed that lower 25(OH)D levels increased the risk of T2DM (Pooled ESRR = 1.34; 95%CI: 1.16, 1.53), Vitamin D supplementation ameliorated FBG (ES = −0.56; 95%CI: −1.00, −0.11), HbA1c (ES = −0.11; 95%CI: −0.20, −0.02), insulin (ES = −0.38; 95%CI: −0.59, −0.18) and HOMA-IR (ES = −0.37; 95%CI: −0.57, −0.16) in T2DM patients, especially in those with Vitamin D deficiency (FBG = −0.98; HbA1c = −0.27; HOMA-IR = −0.52). Conclusion The present umbrella Meta-analyses demonstrates the potential benefits of higher serum Vitamin D levels and Vitamin D supplementation in reducing the development and symptoms of T2DM.